Onboarding : getting new hires off to a flying start - Harpelund, Christian (Emerald Publishing Limited, 2019)
Onboarding of new hires is critical for success today. Employees are increasingly expecting more from companies, and if they don't feel connected and onboard they will likely leave for a new opportunity somewhere else. However, there is a marked lack of knowledge about onboarding at the manager level, and the majority of companies are stuck using a "checklist" approach which does not factor in the emotional experience and engaged integration of the new hire. Onboarding: Getting New Hires off to a Flying Start provides a clear framework for managers to improve the onboarding process. Based on 20 years of experience with recruiting, onboarding, and organisational development, the authors have developed an easy to use model and process for onboarding which maps out 6 dimensions which can be used to design and implement a systematic organizational process. The book also provides real case examples to demonstrate how to take action in an organization and ensure faster and better onboarding of new employees. Outlining specific tools to facilitate the onboarding dialogue between the new employee and the manager, the book will provide immediate solutions to improve and professionalise the discipline of onboarding, leading ultimately to improved new hires' time-to-performance, increasing retention rates, higher engagement, and lower stress-levels.